Viewer Movie Predictions based on Genres, Actors, and Directors based on Data Mining Using the Eclat Algorithm - Deden Muhamad Furqon; Riki Ahmad Maulana; Ahmad Fauzi; Nurul Dwi Cahya; Muhammad Nur Sidiq; Tri Kurnia Sandi (Gunung Djati Conference Series, 2021)
Movies are a place for everyone to find pleasure and entertainment. The film industry is an essential part of the economy in this world. On average, 79% of people in the world enjoy watching movies for their entertainment. Therefore, the film industry has become a huge industry, but it is difficult to predict because the audience's desires are very diverse. Therefore, we created a prediction system for user choices based on the recommendations that will be presented, most likely to be enjoyed by audiences based on genre, actor, and their favorite director, which will function for producers to analyze the market. The method used is data mining using the Eclat algorithm, which has five processes in it. The result is that we get and sort 5043 data by 28 columns and omit some with a support threshold of 0.003 and evaluate the results after evaluating the film data obtained from 1169 lines with a value above 0.003 supporting data to predict user choice recommendations.